2016
DOI: 10.1051/0004-6361/201628541
|View full text |Cite
|
Sign up to set email alerts
|

The IACOB project

Abstract: Context. The term 'macroturbulence' of O-and B-type stars is commonly used to refer to a source of non-rotational broadening affecting their spectral line-profiles. It has been proposed to be a spectroscopic signature of the presence of stellar oscillations; however, we still lack a definitive confirmation of this hypothesis. Aims. We aim to provide new empirical clues about macroturbulent spectral line broadening in O-and B-type stars to evaluate its physical origin. Methods. We use high-resolution spectra of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
124
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 67 publications
20
124
0
1
Order By: Relevance
“…This code characterizes the additional broadening in the line profiles combining Fourier transform and goodness-of-fit methodologies. The obtained velocities (see Table 2) are qualitatively in agreement with velocities measured by Simón-Díaz et al (2017) in stars at the similar evolutionary stages (see their fig. 5).…”
Section: Spectral Modelling and Stellar Parameterssupporting
confidence: 87%
“…This code characterizes the additional broadening in the line profiles combining Fourier transform and goodness-of-fit methodologies. The obtained velocities (see Table 2) are qualitatively in agreement with velocities measured by Simón-Díaz et al (2017) in stars at the similar evolutionary stages (see their fig. 5).…”
Section: Spectral Modelling and Stellar Parameterssupporting
confidence: 87%
“…We note that for spectra with lower S /N ratios, when the line wings are not well defined, the ζ mac -values tend to be less accurate. The ζ mac values also tend to be lower than 20 km s −1 , with only a few stars reaching values up to about 50 km s −1 , which are typical values for massive OB stars (Simón-Díaz, S. et al 2017). We stress that the sample is biased to slow rotators by design, that is, most stars of our sample have v · sin i < 50 km s −1 to allow for a proper detailed elemental abundance study.…”
Section: Comparisons With Other Studiesmentioning
confidence: 79%
“…This wealth of spectroscopic data provides new insights on stellar evolution compared to previous photometric studies, thus providing the required empirical constraints (e.g. Martins & Palacios 2017;Ramírez-Agudelo et al 2017;Sabín-Sanjulián et al 2017;Simón-Díaz et al 2017). In Castro et al (2014), we showed how it is possible to highlight patterns in the spectroscopic Hertzsprung-Russell diagram (sHRD; L ≡ T 4 eff /g, Langer & Kudritzki 2014) and proposed empirical anchors, such as the position of the zero age main-sequence (ZAMS) and of the terminal age main-sequence (TAMS), based on large collections of stellar atmosphere studies in the Milky Way.…”
Section: Introductionmentioning
confidence: 99%